PREDICTING ECONOMIC BEHAVIOR BASED ON ECONOMICS EDUCATION IN THE FAMILY AND UNIVERSITY BY MEDIATING ECONOMIC LITERACY - farideh nasiri; sakineh jafari (آموزش مهندسی ایران, 2025)
The aim of the present study was to investigate the casual relationship between economics education in the family and university and economic behavior of engineering students by mediating economic literacy. This study was an applied research in terms of the purpose and was a type of descriptive-correlational studies based on structural modeling in terms of data collection method. The statistical population of the study consisted of all engineering students of Semnan University (1700 people) in the academic year 2023-2024 who 220 people were selected as study sample using stratified random sampling. The study instrument included economic behavior, economic literacy, economics education in the family and economics education in the university questionnaires. The collected data were analyzed by descriptive statistics (frequency, mean and standard deviation) and inferential statistics (Pearson and path analysis). The results obtained from the data indicate that economics education in the family has a significant effect on economic literacy and economic behavior of engineering students. Economics education in the university has a significant impact on economic literacy and economic behavior of engineering students. Economic literacy has a significant influence on economic behavior of engineering students. Economics education in the family has a significant positive indirect effect on economic behavior of engineering students through mediation of economic literacy. Also, economics education in the university has a significant positive indirect impact on economic behavior of engineering students through mediation of economic literacy. The results of the study show the importance of economics education in the family and university in economic literacy and consequently on the economic behavior of engineering students.